2018
DOI: 10.14414/tiar.v8i2.1313
|View full text |Cite
|
Sign up to set email alerts
|

The effect of firm size, financial ratios and cash flow on stock return

Abstract: Stocks are kinds of financial instruments with high returns that have high levels of uncertainty. Before decide to invest the investor needs to formulate the expected rate of return. Companies with good financial performance will increase the value of the company so that the company's stock price increases and stock return also increases. The purpose of this research was to determine the effect of Firm Size, Return On Equity, Market Book Ratio, Current Ratio, Cash Flow from Operating Activities, Cash Flow from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 0 publications
5
15
2
4
Order By: Relevance
“…In essence, market value shows how market participants as a whole assess the value of a stock and not in terms of company size. The results of this study are in line with studies [40], where firm size cannot moderate the relationship between market value and firm value. In line with the study results [8], market value shows how the overall market behavior is assessed or reflected on the stock and not on the company's size.…”
Section: Path Coefficients Analysissupporting
confidence: 91%
“…In essence, market value shows how market participants as a whole assess the value of a stock and not in terms of company size. The results of this study are in line with studies [40], where firm size cannot moderate the relationship between market value and firm value. In line with the study results [8], market value shows how the overall market behavior is assessed or reflected on the stock and not on the company's size.…”
Section: Path Coefficients Analysissupporting
confidence: 91%
“…The agency theory advocated that large and highly leveraged companies are expected to have better online disclosure (Basuony et al , 2020). In addition, company performance can also be influenced by the company’s size, as large sizes have good business continuity and the ability to attract investors (Yuliarti and Diyani, 2018). Moreover, some studies showed that large companies had a significant positive influence on corporate value (Suhadak et al , 2019a; Husna and Satria, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Firm value is critical since it reflects a firm's performance and can influence investors' perceptions of that company. A strong company value will lead the market to believe in the business's current situation or future prospects [3]. The price of shares traded on the stock exchange is a measure of company value for companies that issue shares in the capital market.…”
Section: Literature Review a Corporate Values: Concepts And Theoriesmentioning
confidence: 99%